Removal of Displaced Maxillary Third Molar Using Modified Gillie's Temporal Approach - Shruthi, T. M. (Ann Maxillofac Surg, 2020)
Tooth impaction is a pathological situation where a tooth is unable to achieve its normal functional position within the expected time span. The removal may be associated with intra-operative or post-operative complications. The Le Fort I osteotomy is a procedure used by maxillofacial surgeons to correct a wide range of dentofacial deformities. Due to its versatility and simplicity, it has gained popularity for a wide range of uses. This case report describes the location and surgical removal of a right maxillary third molar which was accidentally displaced into the infratemporal fossa in a 26-year-old female while performing Le Fort I osteotomy. The patient underwent a second surgery for the retrieval of tooth using modified Gillie's temporal approach. The important role of the cone beam computed tomography in determining the localization of the displaced tooth is demonstrated.